OPTIMALISASI MANAJEMEN KEUANGAN SEKOLAH DALAM PENGGUNAAN DANA BOS UNTUK MENINGKATKAN KINERJA GURU SEKOLAH DASAR - Darpansyah Putra; Aziddin Harahap; Marlina Siregar; Sakinah Ubudiyah Siregar; Junita Junita (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT The urgency of effective management of School Operational Assistance (BOS) funds is a crucial factor in supporting teacher performance and improving the quality of learning. This study aims to analyze the management of BOS funds at SDN 43 Bilah Hulu, identify the challenges encountered, and formulate strategies to optimize school financial management. The study employed a descriptive qualitative approach through observation, interviews, and documentation involving the principal, treasurer, teachers, operator, and school committee as informants. Data were analyzed through data condensation, data display, and conclusion drawing, supported by source and technique triangulation. The results indicate that BOS fund management has been carried out systematically through planning, organizing, implementation, and supervision functions that are participatory, well-directed, and accountable. The funds are utilized for providing learning facilities, technology-based media, and enhancing teachers’ competencies through training and teacher working groups (KKG). The main challenges include limited funds, prioritization of budget allocation, managerial capacity, and issues in supervision and reporting. Optimization strategies are implemented through participatory planning, prioritizing learning quality, strengthening supervision, and ensuring transparency and accountability. The study concludes that the success of BOS fund utilization is largely determined by the school’s managerial capacity in setting priorities, building coordination, and maintaining accountability, which in turn has a tangible impact on teacher performance and the quality of learning. ABSTRAK Urgensi pengelolaan dana Bantuan Operasional Sekolah (BOS) yang efektif menjadi faktor penting dalam mendukung kinerja guru dan peningkatan mutu pembelajaran. Fokus penelitian ini adalah menganalisis pengelolaan dana BOS di SDN 43 Bilah Hulu, mengidentifikasi kendala yang dihadapi, serta merumuskan strategi optimalisasi manajemen keuangan sekolah. Penelitian menggunakan pendekatan kualitatif deskriptif melalui observasi, wawancara, dan dokumentasi dengan kepala sekolah, bendahara, guru, operator, dan komite sekolah sebagai informan. Analisis data dilakukan melalui kondensasi data, penyajian data, dan penarikan kesimpulan dengan triangulasi sumber dan teknik. Hasil penelitian menunjukkan bahwa pengelolaan dana BOS telah dilaksanakan secara sistematis melalui fungsi perencanaan, pengorganisasian, pelaksanaan, dan pengawasan yang partisipatif, terarah, serta akuntabel. Pemanfaatan dana diarahkan pada penyediaan sarana pembelajaran, media berbasis teknologi, serta pengembangan kompetensi guru melalui pelatihan dan KKG. Kendala utama meliputi keterbatasan dana, penentuan prioritas anggaran, kemampuan manajerial, serta tantangan dalam pengawasan dan pelaporan. Strategi optimalisasi dilakukan melalui perencanaan partisipatif, prioritas pada mutu pembelajaran, penguatan pengawasan, serta penerapan transparansi dan akuntabilitas. Simpulan penelitian menegaskan bahwa keberhasilan pemanfaatan dana BOS ditentukan oleh kapasitas manajerial sekolah dalam menetapkan prioritas, membangun koordinasi, dan menjaga akuntabilitas sehingga berdampak nyata pada kinerja guru dan kualitas pembelajaran.